2013
DOI: 10.1021/jp408721e
|View full text |Cite
|
Sign up to set email alerts
|

AuSn20 Eutectic Electrodeposition through Alternative Complexing of Pyrophosphoric Acid: Insights from Electrochemical and DFT Methods

Abstract: Eutectic AuSn20 solder is an important material for electronic packaging technology due to its superior mechanical and thermal conductive properties. In this work, AuSn20 alloy films are prepared via the electrodeposition method for the first time. The electrodeposition is cost-effective with improved control over the alloy content when compared to traditional powdered metallurgy methods. Pyrophosphoric acid was found to be an effective complexing agent to minimize the difference of the deposition potentials b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Complexing agents can reduce the deposition potential difference between the desired metal ions to a great extent, which is the key factor in realizing co-deposition of Au-Sn. 15 Therefore, to choose effective complex agents is critical for the co-deposition of Au-Sn alloys. Ivey et al 12 reported a non-cyanide Au-Sn co-electroplating solution containing Au(III) and Sn(II) chloride salts with ammonium citrate and sodium sulfite as complexing agents.…”
mentioning
confidence: 99%
“…Complexing agents can reduce the deposition potential difference between the desired metal ions to a great extent, which is the key factor in realizing co-deposition of Au-Sn. 15 Therefore, to choose effective complex agents is critical for the co-deposition of Au-Sn alloys. Ivey et al 12 reported a non-cyanide Au-Sn co-electroplating solution containing Au(III) and Sn(II) chloride salts with ammonium citrate and sodium sulfite as complexing agents.…”
mentioning
confidence: 99%